Associations of Serum ALB, IL-18, and NGAL Levels and Individualized Nutritional Nursing in Patients with Hematopoietic Stem Cell Transplantation and Myelosuppression - Yu Wu; Lei Geng (Pakistan Journal of Medical Sciences, 2026)
Objective: To investigate the clinical associations of serum albumin (ALB), interleukin-18 (IL-18), and neutrophil gelatinase-associated lipocalin (NGAL) and individualized nutritional nursing on the recovery of patients in the myelosuppression stage of the conditioning regimen of hematopoietic stem cell transplantation (HSCT). Methodology: Retrospectively selecting clinical data of 118 patients undergoing hematopoietic stem cell transplantation First Affiliated Hospital of Soochow University, Department of Hematology, from January 2024 to September 2025, 56 patients receiving routine care from January 2024 to November 2024 were selected as the control group, and 62 patients receiving personalized nutritional nursing from December 2024 to September 2025 were selected as the study group. Dynamics of serum ALB, IL-18, and NGAL were tested. Statistics on hematopoietic function reconstruction, serological indicators, complications, and hospitalization-related indicators during the bone marrow suppression period in two groups. Results: The study group had lower neutrophil implantation time, platelet implantation time, red blood cell transfusion volume, and platelet transfusion volume compared to the control group (P0.05). Conclusion: Individualized nutritional nursing can accelerate the reconstruction of bone marrow hematopoietic function and may reduce the incidence of complications, and shorten the length of hospital stay, potentially through modulation of serum ALB, IL-18, and NGAL levels during the conditioning regimen of HSCT.